Infertility knowledge and treatment beliefs among African American women in an urban community - Ashley Wiltshire; Lynae M Brayboy; Kiwita Phillips; Roland Matthews; Fengxia Yan; Desiree McCarthy-Keith (BMC, 2019)
Abstract Background To assess infertility knowledge and treatment beliefs among African American women in an urban community in Atlanta, Georgia. Methods This was a cross sectional study at a safety net hospital. A convenience sample of a total of 158 women receiving outpatient obstetrical or gynecologic care from March-April 2017 were recruited. Infertility knowledge and treatment beliefs were assessed using a previously applied and field-tested survey from the International Fertility Decision Making Study. Results The mean infertility knowledge score was 38.15% for total subjects. Those with a higher level of education (p < 0.0001) and those with paid employment (p = 0.01) had a significantly higher level of infertility knowledge. Those who had a history of infertility therapy were significantly more likely to agree with negative treatment beliefs (p = 0.01). There was no significant difference in infertility knowledge or treatment beliefs based on age, sexuality, parity or being pregnant at the time of survey completion. Conclusions African American women in our urban clinic setting seem to have a limited level of knowledge pertaining to infertility. Further research is needed to understand how differences in knowledge and beliefs translate into infertility care decision-making and future childbearing.